Analyzing the nexus between tourism and CO2 emissions: the role of renewable energy and R&D - Balli, Erdinc; Cengiz, Orhan; Koca Balli, Ayse Ipek; Akar, Basak Gul (Frontiers in Environmental Science, 2023)
This study aims to investigate the relationship between tourism development, renewable energy consumption (REN), research & development expenditure (R&D), and CO 2 emissions in 12 Emerging Markets and Middle-Income Europe spanning the period 1999-2020. We applied the panel autoregressive distributed lag (ARDL) and the Driscoll-Kraay estimator to determine the relationship between variables. According to both estimators' results, a U-shaped relationship exists between economic growth and CO 2 emissions. This result indicates that the environmental Kuznets curve (EKC) hypothesis is invalid in these countries. Furthermore, REN and R&D contribute to decreasing CO 2 emissions and stimulating sustainable development. However, the impact of tourism development on CO 2 emissions is found negative in panel ARDL but positive in the Driscoll & Kraay estimator for fixed and random effects. Moreover, the Dumitrescu and Hurlin panel causality test reveals a two-way causal relationship between R&D and CO 2 emissions and a one-way causal linkage running from economic growth, the square of economic growth, and tourist arrival to CO 2 emissions. Overall, our results prove the existence of the relationship between international tourism and CO 2 emissions. Besides, our results suggest some policy recommendations for the policymakers to reduce CO 2 emissions through REN, R&D, green economic development, and establishing an ecologically friendly tourism policy.